2018
DOI: 10.1139/cjfas-2017-0302
|View full text |Cite
|
Sign up to set email alerts
|

Predator–prey dynamics mediate long-term production trends of cisco (Coregonus artedi) in a northern Wisconsin lake

Abstract: We quantified production, biomass, and production to biomass (P/B) ratios for cisco (Coregonus artedi) in Trout Lake, Wisconsin, USA (2001–2015). Across all years, annual production, biomass, and P/B were variable ranging 0.6–30.2 kg·ha−1·year−1, 1.2–39.7 kg·ha−1, and 0.4–0.9·year−1, respectively. Cisco production exhibited obvious decline. However, neither biomass nor P/B changed significantly over time. Long-term patterns of environmental conditions remained unchanged during the study and were unrelated to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…All rights reserved. (Hansen et al, 2017), to climate and trophic interactions (Parks & Rypel, 2018), and to disturbance and vegetation change (Dodds et al, 2012). Initial studies indicate that eDNA can be used in conjunction with long-term monitoring of fish populations in lakes (Klobucar et al, 2017).…”
Section: Accepted Articlementioning
confidence: 99%
“…All rights reserved. (Hansen et al, 2017), to climate and trophic interactions (Parks & Rypel, 2018), and to disturbance and vegetation change (Dodds et al, 2012). Initial studies indicate that eDNA can be used in conjunction with long-term monitoring of fish populations in lakes (Klobucar et al, 2017).…”
Section: Accepted Articlementioning
confidence: 99%
“…Two-story lakes are deep stratified lakes with sufficient oxythermal habitat to support both warmwater and coldwater fisheries (Lyons et al 2017a;Parks and Rypel 2018). In Wisconsin, "two-story lakes" receive additional protection in the form of more stringent phosphorus water quality standards.…”
Section: Special Casesmentioning
confidence: 99%
“…In Wisconsin, "two-story lakes" receive additional protection in the form of more stringent phosphorus water quality standards. Two-story lakes are deep stratified lakes with sufficient oxythermal habitat to support both warmwater and coldwater fisheries (Lyons et al 2017a;Parks and Rypel 2018). Two-story lakes were included in the tier-one cluster analysis, therefore, we combined results from that analysis with the existing two-story list to produce two terminal lake classes termed "simple-two-story," and "complex-two-story" lakes.…”
Section: Special Casesmentioning
confidence: 99%
“…Cisco have been shown to influence lake trout ( Salvelinus namaycush , Walbaum) production (Parks & Rypel, ), and the presence/absence of cisco has had variable influences on walleye maximum growth potential (Kaufman et al, ; Noring et al, in press). Anecdotal angler reports have suggested that muskellunge population size structure and maximum size is higher in waters with cisco present.…”
Section: Introductionmentioning
confidence: 99%
“…Cisco have been shown to influence lake trout (Salvelinus namaycush, Walbaum) production (Parks & Rypel, 2018), and the presence/absence of cisco has had variable influences on walleye maximum growth potential (Kaufman et al, 2009;Noring et al, in press).…”
Section: Introductionmentioning
confidence: 99%